2017
DOI: 10.1016/j.toxicon.2016.11.260
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of local effects induced by Bothrops erythromelas snake venom: Assessment of the effectiveness of Brazilian polyvalent bothropic antivenom and aqueous leaf extract of Jatropha gossypiifolia

Abstract: Bothrops erythromelas is a snake of medical importance responsible for most of the venomous incidents in Northeastern Brazil. However, this species is not included in the pool of venoms that are used in the Brazilian polyvalent bothropic antivenom (BAv) production. Furthermore, it is well known that antivenom therapy has limited efficacy against venom-induced local effects, making the search for complementary alternatives to treat snakebites an important task. Jatropha gossypiifolia is a medicinal plant widely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Anyway, some studies have shown the potentiality of some vegetal species acting in two ways: directly, neutralizing venom toxins, or indirectly, by having some of the pharmacological activities mentioned above. For example, Jatropha gossypiifolia (Euphorbiaceae), a plant species studied very much in our research group, showed significant antiophidic properties, inhibiting biological and enzymatic activities from Bothrops venoms [ 96 , 119 ], and presented anti-inflammatory, antioxidant, anticoagulant, and antimicrobial properties in preclinical assays [ 81 ]. So, plants which possess these biological activities determined in previous studies might be preferred or prioritized in studies searching for antiophidic plants.…”
Section: Antivenom Activities Of Extracts Of Medicinal Plants Agaimentioning
confidence: 99%
“…Anyway, some studies have shown the potentiality of some vegetal species acting in two ways: directly, neutralizing venom toxins, or indirectly, by having some of the pharmacological activities mentioned above. For example, Jatropha gossypiifolia (Euphorbiaceae), a plant species studied very much in our research group, showed significant antiophidic properties, inhibiting biological and enzymatic activities from Bothrops venoms [ 96 , 119 ], and presented anti-inflammatory, antioxidant, anticoagulant, and antimicrobial properties in preclinical assays [ 81 ]. So, plants which possess these biological activities determined in previous studies might be preferred or prioritized in studies searching for antiophidic plants.…”
Section: Antivenom Activities Of Extracts Of Medicinal Plants Agaimentioning
confidence: 99%
“…This is particularly important for individuals with diabetes suffering from chronic wounds [29]. The previous studies have revealed the existence of hyaluronidase inhibitors in P. granatum, C. sinensis [30]. However, hyaluronidase inhibitory activity was not reported in P. lentiscus leaves, P. dactylifera seeds and C. comosum leaves extract so, these plants considered as new potential sources for hyaluronidase inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…The only authorized and effective treatment for snake envenomation is anti-snake venom (Ahmad et al, 2020). However, this treatment is expensive and requires ideal storage facilities (Abubakar et al, 2023), which may not be available in rural communities of developing countries (Felix-Silva et al, 2017).…”
Section: Venomous Snakesmentioning
confidence: 99%